Kasnak Meşesi (Quercus Vulcanica (Boiss. And Heldr. Ex) Kotschy)’nin Türkiye’deki İkinci Yeni Bir yayılış Alanı - Aydınözü, Duran (Marmara Coğrafya Dergisi Sayı.9, Ocak, İstanbul., 2004)
The spreading area of Quercus vulcanica in Turkey, which is an endemic species of our country is limited. This new spreading area of this Quercus species in northern Anatolion mountains facing an increasing danger of extinction as a result of unconscious destruction has been discovered by us by the existing literature.
The second newly spread area of Quercus vulcanica (Boiss and Heldr. Kotschy in Turkey
Keywords: Kasnak meşesi